2017
DOI: 10.1097/qad.0000000000001553
|View full text |Cite
|
Sign up to set email alerts
|

Sexual partnership age pairings and risk of HIV acquisition in rural South Africa

Abstract: Objective:To quantify the contribution of specific sexual partner age groups to the risk of HIV acquisition in men and women in a hyperendemic region of South Africa.Design:We conducted a population-based cohort study among women (15–49 years of age) and men (15–55 years of age) between 2004 and 2015 in KwaZulu-Natal, South Africa.Methods:Generalized additive models were used to estimate smoothed HIV incidence rates across partnership age pairings in men and women. Cox proportional hazards regression was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
70
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 45 publications
(58 reference statements)
10
70
1
Order By: Relevance
“…HIV incidence was found to increase with increasing age and recent infection was highest at younger ages and long-term infections were common in older ages. These findings are consistent with many South African data which aims to understand the risk factors for HIV infection in men (Jewkes et al, 2006) and assessing sexual partnership and age pairing as a risk of HIV acquisition (Akullian et al, 2017), however, these are based on epidemiological data without the use of formal network designs. In sexual networks, the younger ages identified to be associated with HIV infection suggested that while low HIV prevalence is observed in young males, their risk to new HIV infections is similar to their female counterparts (Zeh et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…HIV incidence was found to increase with increasing age and recent infection was highest at younger ages and long-term infections were common in older ages. These findings are consistent with many South African data which aims to understand the risk factors for HIV infection in men (Jewkes et al, 2006) and assessing sexual partnership and age pairing as a risk of HIV acquisition (Akullian et al, 2017), however, these are based on epidemiological data without the use of formal network designs. In sexual networks, the younger ages identified to be associated with HIV infection suggested that while low HIV prevalence is observed in young males, their risk to new HIV infections is similar to their female counterparts (Zeh et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Further, husbands or males are found to have the highest number of reported sexual partners and may result in higher transmission probabilities and unlinked cases are the internal source of infection and have occasional sexual relationships as an external source of infection. Current epidemiological data indicate sexual partnerships are an important risk factor for HIV infection in South Africa (Akullian et al, 2017;Beauclair, Hens, & Delva, 2015;Kalichman et al, 2013), however at this point, it is not clear whether sequential or concurrent relationships pose similar or different risks to sexual partners. In this review, we report on sexual partnerships as an important risk factor which warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous reports , all distribution models had high male participation in each country. Strategies that provide men with greater coverage of HIV testing and care are urgently needed both to address the disproportionately high testing gap and mortality from HIV in men, and also to reduce risk of onward transmission of HIV . Peak HIV prevalence for men in southern Africa is now in the 40‐ to 49‐year‐old age‐group , with older men among least likely to have accessed standard HIV testing services .…”
Section: Discussionmentioning
confidence: 99%
“…These large sample sizes taken from a complete population followed longitudinally for well over a decade permit powerful statistical inference. This in turn can facilitate a deep and nuanced understanding of underlying causal risk factors and processes and a quantification of dynamic incidence patterns among different population sub-strata allowing for identification of particularly vulnerable sub-groups [39][40][41][42].…”
Section: Overview Of the Ahri Population-based Cohortmentioning
confidence: 99%